2016
DOI: 10.1080/07448481.2016.1185725
|View full text |Cite
|
Sign up to set email alerts
|

Personalized boosters for a computerized intervention targeting college drinking: The influence of protective behavioral strategies

Abstract: Objective Computerized interventions are cost-effective and can quickly deliver individual feedback to many students. However, in-person interventions are more efficacious. The current study sought to improve the efficacy of a popular online intervention via emailed boosters with personalized feedback. Participants Participants were 213 student drinkers at a southeastern public university, ages 18–24. Methods Students were randomized into: 1) intervention only, or 2) intervention plus booster. Alcohol cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 54 publications
2
53
0
Order By: Relevance
“…One such strategy may be the administration of booster follow-up sessions. The implementation and evaluation of the incremental benefit of booster sessions over the initial intervention remains relatively unexplored in brief alcohol interventions with the exception of only a small handful of studies to date with mixed results (e.g., Braitman & Henson, 2016; Caudill et al, 2007; Longabaugh et al, 2001). Many questions remain to assess the application of boosters to enhance initial intervention effects including when it is best to administer the booster, what the ideal dosing is (number and length of sessions), and what is the best modality of the booster (e.g., in-person, phone check-ups, text messaging).…”
Section: Discussionmentioning
confidence: 99%
“…One such strategy may be the administration of booster follow-up sessions. The implementation and evaluation of the incremental benefit of booster sessions over the initial intervention remains relatively unexplored in brief alcohol interventions with the exception of only a small handful of studies to date with mixed results (e.g., Braitman & Henson, 2016; Caudill et al, 2007; Longabaugh et al, 2001). Many questions remain to assess the application of boosters to enhance initial intervention effects including when it is best to administer the booster, what the ideal dosing is (number and length of sessions), and what is the best modality of the booster (e.g., in-person, phone check-ups, text messaging).…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the limited number of PBS addressed in the Direct and Indirect PBS conditions or measurement limitations. More sensitive, multi-faceted assessment of PBS may be needed to detect intervention effects, including more frequent assessment of PBS use to enhance accuracy; scales more sensitive than 7-point Likert scales (Braitman, 2012); and measurement of related constructs along with frequency of PBS use. Self-efficacy to use PBS has been linked to less alcohol use in survey research (Bonar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Cunningham et al [ 34 ] compared a brief with an extended intervention (AlcoholHelpCentre.net) and found that the extended intervention did not increase the effect. In recent studies, however, promising results have been obtained from adding new elements to standard interventions, such as gamification [ 35 ], booster email sessions [ 36 , 37 ], skills training via mobile phone apps [ 38 ], individually tailored text messaging [ 39 ], and Facebook delivery of personalized normative feedbacks [ 40 ].…”
Section: Introductionmentioning
confidence: 99%